2014
DOI: 10.1055/s-0034-1382961
|View full text |Cite
|
Sign up to set email alerts
|

Amide Alkaloids from Scopolia tangutica

Abstract: Four new hydroxycinnamic acid amides, scotanamines A?D (1?4), and seven known alkaloids, including N 1,N 10-di-dihydrocaffeoylspermidine (5), scopolamine (6), anisodamine (7), hyoscyamine (8), anisodine (9), caffeoylputrescine (10), and N 1-caffeoyl-N 3-dihydrocaffeoylspermidine (11), were obtained from the roots of Scopolia tangutica. The present study represents the first recognition of hydroxycinnamic acid amides containing putrescine or spermidine in S. tangutica. Compound 1, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Eleven alkaloids have been isolated from S. tangutica [11, 12]. They include seven HCA amides (1-7): scotanamine A-D (1-4), N 1 , N 10 -di-dihydrocaffeoylspermidine (5), cafeoylputrescine (6), N 1 -caffeoyl-N 3 -dihydrocaffeoylspermidine (7), one cinnamic acid amide: carboxyscotangamine A (8) and three well-known anticholinergic compounds (9-10): scopolamine (9), atropine (10) and anisodine (11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven alkaloids have been isolated from S. tangutica [11, 12]. They include seven HCA amides (1-7): scotanamine A-D (1-4), N 1 , N 10 -di-dihydrocaffeoylspermidine (5), cafeoylputrescine (6), N 1 -caffeoyl-N 3 -dihydrocaffeoylspermidine (7), one cinnamic acid amide: carboxyscotangamine A (8) and three well-known anticholinergic compounds (9-10): scopolamine (9), atropine (10) and anisodine (11).…”
Section: Resultsmentioning
confidence: 99%
“…An aliquot of 0.1 mL of crude extract sample was applied to the conditioned SCX-based solid phase extraction column. The isolation and identification of pure compounds from S. tangutica are extensively described by our most recent report [12]. Briefly, S. tangutica were extracted by 95% ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elucidation and specific assignments of these compounds were in supporting information. Other known compounds are isolated as scopolamine3940 ( 1 ), anisodamine4142 ( 2 ), hyoscyamine4344 ( 3 ), anisodine31 ( 4 ), N-Caffeoylputrescine364546 ( 14 ), N1,N10-di-dihydrocaffeoylspermidine2147 ( 17 ), Scotanamine D21 (19), and N1-caffeoyl-N3-dihydrocaffeoyl spermidine48 ( 20 )…”
Section: Resultsmentioning
confidence: 99%
“…First, traditional approaches such as solvent extraction followed by thin-layer chromatography1415 or one-dimensional (1D) high performance liquid chromatography-mass spectrometry (HPLC-MS)161718 often result in isolation and identification of small sets of compounds because of the chemical diversity of many medicinal plants. Second, our recent non-aqueous solid phase extraction (SPE)19 and 2D-HPLC methods20 have resulted in the identification of four hydroxycinnamic acid amides from S. tangutica for the first time21. This study also suggested the presence of a large number of minor alkaloids.…”
mentioning
confidence: 80%